2020
DOI: 10.1155/2020/8712407
|View full text |Cite
|
Sign up to set email alerts
|

The Synchronization of Electron Enricher and Electron Extractor as Ternary Composite Photoanode for Enhancement of DSSC Performance

Abstract: This work developed a novel ternary composite photoanode of dye-sensitized solar cell (DSSC) composed of (i) N-, S-doped titanium dioxide with exposed {001} facet (N-, S-TiO2{001}), (ii) N-, S-doped reduced graphene oxide (N-, S-rGO), and (iii) commercial titanium dioxide (P25). The DSSC device fabricated with the ternary composite photoanode showed the greatest of power conversion efficiency (8.62%) compared to the device fabricated with P25 photoanode (3.20%). This enhancement was attributed to the synergist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This impressive result is possibly due to the mesostructure in 3DOM. Photocatalysts with high dye-loading capacity are also desirable for other applications such as dye-sensitized solar cells (DSSC), [ 49 , 50 , 51 , 52 ] highlighting the potential utilization of our developed catalysts in other applications. The photocatalytic efficiency of the 3D-HPT was also compared with the commercial anatase TiO 2 and no catalysts, and the results are presented in Figure 5 a.…”
Section: Resultsmentioning
confidence: 99%
“…This impressive result is possibly due to the mesostructure in 3DOM. Photocatalysts with high dye-loading capacity are also desirable for other applications such as dye-sensitized solar cells (DSSC), [ 49 , 50 , 51 , 52 ] highlighting the potential utilization of our developed catalysts in other applications. The photocatalytic efficiency of the 3D-HPT was also compared with the commercial anatase TiO 2 and no catalysts, and the results are presented in Figure 5 a.…”
Section: Resultsmentioning
confidence: 99%
“…These peaks represent the photoemission of free electrons that recombined at the shallow trap states due to oxygen vacancies. [32][33] Moreover, it was found that PL intensity increased with an increase in particle size of Au NPs. According to Kodiyath's group, this was attributed to the recombination of hot electrons generated by the LSPR process.…”
Section: Characterizations Of Au Nps Deposited On Tio 2 {001}-{010}mentioning
confidence: 98%
“…In this context, TiO 2 is used for photocatalysis as they are candidates for a wide range of applications such as hydrogen production, gas sensors, and supercapacitors [17], a property of great interest in dye-sensitized solar cells, where the dye is used together with a photocatalyst, which can be a semiconductor oxide such as TiO 2 or zinc oxide (ZnO) [17,20].…”
Section: Photocatalysismentioning
confidence: 99%
“…All anthocyanins are derived from specific. The core of the chromophore, phenylbenzopyridine or flavin, consists of two aromatic rings (see Figure 9) [20,58].…”
Section: Anthocyanidinsmentioning
confidence: 99%